Comparing the linear and logarithm normalized extreme learning machine in flow curve modeling of magnetorheological fluid - Irfan Bahiuddin; Abdul Y Abd Fatah; Saiful A Mazlan; Mohd I Shapiai; Fitrian Imaduddin; Ubaidillah Ubaidillah; Dewi Utami; Mohd N Muhtazaruddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The extreme learning machine (ELM) plays an important role to predict magnetorheological (MR) fluid behavior and to reduce the computational fluid dynamics (CFD) calculation cost while simulating the MR fluid flow of an MR actuator. This paper presents a logarithm normalized method to enhance the prediction of ELM of the flow curve representing the MR fluid rheological properties. MRC C1L was used to test the performance of the proposed method, and different activation functions of ELMs were chosen to be the neural networks setting. The Normalized Root Mean Square Error (NRMSE) was selected as the indicator of the ELM prediction accuracy. NRMSE of the proposed method is found to improve the model accuracy up to 77.10 % for the prediction or testing case while comparing with the linear normalized ELM